The liquidity channel of fiscal policy - Christian Bayer; Benjamin Born; Ralph Luetticke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
We provide evidence that expansionary fiscal policy lowers return differences between public debt and less liquid assets-the liquidity premium. We rationalize this finding in an estimated heterogeneous-agent New-Keynesian model with incomplete markets and portfolio choice, in which public debt affects private liquidity. This liquidity channel stabilizes fixed-capital investment. We then quantify the long-run effects of higher public debt and find little crowding out of capital, but a sizable decline of the liquidity premium, which increases the fiscal burden of debt. We show that the revenue-maximizing level of public debt is positive and has increased to 60 percent of GDP post-2010.
Keywords: C11; D31; E21; E32; E63; 330; Business cycles; fiscal policy; HANK; incomplete markets; liquidity premium; public debt